1992
DOI: 10.1038/355848a0
|View full text |Cite
|
Sign up to set email alerts
|

Genetically modified photosynthetic antenna complexes with blueshifted absorbance bands

Abstract: Light energy for photosynthesis is collected by the antenna system, creating an excited state which migrates energetically 'downhill'. To achieve efficient migration of energy the antenna is populated with a series of pigments absorbing at progressively redshifted wavelengths. This variety in absorbing species in vivo has been created in a biosynthetically economical fashion by modulating the absorbance behaviour of one kind of (bacterio)chlorophyll molecule. This modulation is poorly understood but has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
231
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(252 citation statements)
references
References 11 publications
21
231
0
Order By: Relevance
“…Accordingly, the charged amino acids do not play the dominant role that was attributed to them in earlier studies (15)(16)(17)28), where large parts of the protein charge distribution, in particular, the backbone, were not modeled, and standard protonation states of titratable residues were assumed (15)(16)(17). In qualitative agreement with experimental results on other antenna systems (29), hydrogen bond donors to BChla cause red shifts of the site energies, but in the present system this shift never exceeds Ϸ130 cm Ϫ1 (SI Table 4). …”
Section: Resultssupporting
confidence: 77%
“…Accordingly, the charged amino acids do not play the dominant role that was attributed to them in earlier studies (15)(16)(17)28), where large parts of the protein charge distribution, in particular, the backbone, were not modeled, and standard protonation states of titratable residues were assumed (15)(16)(17). In qualitative agreement with experimental results on other antenna systems (29), hydrogen bond donors to BChla cause red shifts of the site energies, but in the present system this shift never exceeds Ϸ130 cm Ϫ1 (SI Table 4). …”
Section: Resultssupporting
confidence: 77%
“…Alternatively, Fowler et al (1992) have recently shown that the red shifts associated with some photosynthetic pigments are due, in part, to T-?T interactions between the chromophore and nearby tyrosine residues. When these tyrosines are replaced by site-directed mutagenesis, the lowest energy T-T* transition of the chromophore is blue shifted by as much as 24 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of protein-Bchla interactions to the red shift of the Bchla Q y transition observed in the LH2 complexes has been extensively studied by resonance Raman spectroscopy [6]. In this regard, it has been especially useful in combination with the technique site-directed mutagenesis, which has been used to create LH complexes with altered spectral properties [7,8].…”
Section: Introductionmentioning
confidence: 99%